2018
DOI: 10.3389/fpsyg.2018.01500
|View full text |Cite
|
Sign up to set email alerts
|

30 Days Wild and the Relationships Between Engagement With Nature’s Beauty, Nature Connectedness and Well-Being

Abstract: Recent research suggests that engagement with natural beauty (EWNB) is key to the well-being benefits of nature connectedness. The Wildlife Trust’s 30 Days Wild campaign provides a large-scale intervention for improving public engagement with nature and its beauty. The effect of 30 Days Wild participation on levels of EWNB and the relationship between EWNB, nature connectedness and happiness was evaluated during the 2017 campaign. Of the 49,000 people who signed up to the campaign, 308 people fully completed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 42 publications
(71 reference statements)
6
81
0
2
Order By: Relevance
“…As an affect-based approach was taken to the development of the NCI this would be expected and indicates utility as a measure to evaluate an affective connection with nature. The relationship to affect regulation and beauty is important as both have been found to mediate the relationship between nature connectedness and well-being [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As an affect-based approach was taken to the development of the NCI this would be expected and indicates utility as a measure to evaluate an affective connection with nature. The relationship to affect regulation and beauty is important as both have been found to mediate the relationship between nature connectedness and well-being [20].…”
Section: Discussionmentioning
confidence: 99%
“…The 16-item Difficulties in Emotion Regulation Scale (DERS; [51]) was used to indicate ease of affect regulation. It has been found that affect regulation mediates the relationship between nature connectedness and well-being providing, an indication of alternative mechanisms and confirming the importance of affect [20]. Therefore, it is interesting to look at the relationship between affect regulation and nature connectedness.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Utilizing nature relatedness scales opens up a door to provider-patient discourse on possible routes to health and vitality (determining how much active/passive time a patient spends in the outdoors, and the writing of "Green Prescriptions" [124][125][126]); since nature relatedness is also associated with pro-environmental and pro-social attitudes and behaviors-likely because experience in/with the natural world promotes concern for planetary health [127][128][129][130]-assessments allow for discussions concerning a collective "treatment" of personal and global problems, actively engaging both clinician and patient in planetary health [131]. Clinicians now have an opportunity to track nature relatedness with functional aspects of health.…”
Section: Practical Implicationsmentioning
confidence: 99%